Promoting English reading skills through video games: A case study (2024)
The concept of video games has been explored as an entertainment object. However, in recent years, various authors have explored video games' potential in teaching. This research was implemented using an interpretive methodology based on a case study with a population of six students from a public school in the city of Bello. We found the scope of video games and how they promote reading habits from the interviews, workshop records, and questionnaires. Due to the implementation, we confirmed various perspectives on video games and the limitations that exist for an eventual implementation in the Colombian context. Likewise, although video games benefit interaction with reading content, they must be implemented with an educational purpose and according to the students' interests. Finally, this research explores the various perspectives that the participants had regarding the effectiveness of video games in promoting reading habits in a second language, based on the interaction with the video game Life is Strange.